Pengaruh Model Project Based Learning Berbantuan Video Interaktif Terhadap Kemampuan Kreativitas Siswa Sekolah Dasar: Suatu Kajian Sistematis Literatur - Mujadillah (GENFABET: Generasi Pendidikan Dasar, 2025)
This systematic literature review explores the influence of Project based learning (PjBL) supported by interactive video media on the creativity of elementary school students. In the 21st-century educational landscape, creativity is a fundamental skill that must be developed from an early age. The study aims to map current research findings on how the integration of digital interactive videos within PjBL environments contributes to enhancing students' creative thinking dimensions, including originality, elaboration, fluency, and flexibility. A total of 38 relevant empirical articles published between 2015 and 2024 were selected from databases such as Google Scholar, ERIC, Scopus, and ResearchGate. The PRISMA method was used for article selection, and thematic analysis was conducted using NVivo 12 Plus. The results indicate that video-assisted PjBL consistently supports creativity development by stimulating idea generation, contextual understanding, and student engagement. However, challenges such as digital infrastructure, teacher readiness, and time allocation are noted. This study contributes theoretically to creative learning model development and offers practical implications for educators aiming to design meaningful, technology-integrated instructional practices in elementary education.